Pengembangan Model Edukasi Investasi Berbasis Sains untuk Meningkatkan Kesadaran Keuangan dan Kemandirian Finansial Mahasiswa - Andi Hasrun; Masseni Masseni; Rokhimah Rokhimah; Vantri Pieter Kelelufna; Putu Anggreyani Widya Astuti; Arce Y. Ferdinandus; Fitria Hafizah (Universitas 45 Surabaya, 2025)
Students are a group that is developing themselves, both in academic and non-academic aspects, including in financial management. However, low financial literacy among students is one of the main obstacles in planning finances and investments effectively. Financial planning that involves investment can be a solution to achieving financial freedom in the future. Therefore, an educational model is needed that can increase students' interest and understanding of investment. One effective approach is to develop a science-based educational model, which allows students to understand the concept of investment through scientific methods that prioritize logic, analysis, and empirical evidence. With this approach, it is hoped that students can develop skills in planning finances and investments better